2023
DOI: 10.1097/dcr.0000000000002831
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Preoperative Factors in Patients With IBD on Postoperative Length of Stay: A National Surgical Quality Improvement Program–Inflammatory Bowel Disease Collaborative Analysis

Abstract: BACKGROUND: Inflammatory bowel disease patients are challenging to manage peri-operatively due to disease complexity and multiple comorbidities. OBJECTIVE: This study aimed to identify if preoperative factors and operation type were associated with extended postoperative length of stay after inflammatory bowel disease-related surgery, defined by 75 th percentile or greater (n = 926, 30.8%). DESIGN: This was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Patients with IBD are reported to have a longer LOS after colorectal resection than patients with neoplasia or diverticulitis because of their chronic inflammatory state, which is often associated with malnutrition [ 21 , 22 ]. A recent report investigating the details of preoperative medical therapy and postoperative consequences revealed that features that prolong postoperative hospital stay include bleeding disorders, hypoalbuminemia, and ASA score 3–5 [ 23 ]. Our results also showed that the ASA score and age at the time of surgery were independent risk factors for LOS.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with IBD are reported to have a longer LOS after colorectal resection than patients with neoplasia or diverticulitis because of their chronic inflammatory state, which is often associated with malnutrition [ 21 , 22 ]. A recent report investigating the details of preoperative medical therapy and postoperative consequences revealed that features that prolong postoperative hospital stay include bleeding disorders, hypoalbuminemia, and ASA score 3–5 [ 23 ]. Our results also showed that the ASA score and age at the time of surgery were independent risk factors for LOS.…”
Section: Discussionmentioning
confidence: 99%
“…Albumin levels are a significant indicator of nutritional status. 39,40 In comparison with the preoperative albumin levels of the two groups (38.01 AE 4.78 and 42.38 AE 3.8 g/L, respectively), the preoperative albumin level in the blood transfusion group was significantly lower than that in the control group (p < 0.05), possibly due to the patients' poorer nutritional status prior to surgery. Low albumin levels can lead to delayed wound healing and an increased risk of infection.…”
Section: Correlation Between Postoperative Blood Transfusion and Vari...mentioning
confidence: 91%
“…In a very recently published study of a large number of patients (1710 with CD and 1291 with UC), it was found that clinically significant factors contributing to increased postoperative length of hospital stay were rectal surgery, creation of a new ileostomy, preoperative hospitalization, hypoalbuminemia and the presence of bleeding disorder. Of interest was the finding that chronic use of corticosteroids, immunosuppressants, and biological agents including orally administered small molecule drugs, was insignificant[ 13 ]. Another clinical question concerns the possible relationship between serum infliximab (IFX) levels and the presence of endoscopic recurrence in patients undergoing cecal and ileal resection for CD.…”
Section: Surgery For Small Bowel CDmentioning
confidence: 99%